Creating Hospitals’ Core Competencies with Lean Healthcare Strategies Entering the ASEAN Economic Community - Ponanake, Pareeyawadee; ., Manat Pithuncharurnlap; ., Woranat Sangmanee (Journal of Economics and Behavioral Studies, 2014)
This study aimed to evaluate the structural equation modeling of the influences between Lean healthcare strategies, internal quality management and hospitals’ core competencies as medical care centers entering the ASEAN Economic Community. The populations and sample groups in this study included 384 HA officers. The research was conducted from December 2012 to August 2013, and the research method involved purposive sampling through questionnaires. A statistical data analysis was performed using Structural Equation Modeling analysis. This study found that 1) Lean healthcare strategies indirectly influenced hospitals’ core competencies as medical centers entering the ASEAN Economic Community through internal quality management at the 0.01 significance level, 2) Lean healthcare strategies directly influenced hospitals’ core competencies as medical centers entering the ASEAN Economic Community at the 0.01 significance level; 3) Lean healthcare strategies directly influenced internal quality management at the 0.01 significance level; and 4) internal quality management directly influenced hospitals’ core competencies as medical centers entering the ASEAN Economic Community at the 0.01 significance level.